STUDI KOMPUTASI KARAKTERISTIK OPTIK CYANIDIN SEBAGAI SENSITISER DENGAN PELARUT ETHANOL, AIR, DAN ACETONITRILE - Elvan Yuniarti; Ai Nurlaela (Universitas Riau, 2023)
Cyanidin molecule is a type of anthocyanin that has the potential as a sensitizer for dye sensitiser solar cell (DSSC). This molecule is contained in blueberries, grapes, raspberries, and others. This study aims to determine cyanidin molecules' molecular orbitals and HOMO-LUMO energy levels with ethanol, water, and acetonitrile. In addition, this study aims to determine the optical properties of cyanidin dye with ethanol, water, and acetonitrile as solvents. The method used in this research is density functional theory (DFT) and TD-DFT/UB3LYP using Orca.2.02 and quantum espresso applications. The results obtained in the molecular orbitals of cyanidin with various solvents (ethanol, water, acetonitrile) obtained energy gap: 2.8 eV, 2.4 eV, and 3.2 eV. The results of UV-Vis absorption spectra (ethanol, water, acetonitrile) have the same wavelength (158.80 nm – 271.10 nm, 362.10 nm, 453.60 nm) but the intensity is different. Likewise the results of theinfra red spectra (1138 cm-1 – 1486 cm-1), and the Raman spectra (1141 cm-1 – 1606 cm-1) for different solvents have almost the same wave number.